ANALYSIS OF ONLINE PROMO PROGRAMS AND SERVICE QUALITY ON CONSUMER PURCHASING DECISIONS IN SURABAYA THROUGH TRUST IN SHOPEE E-COMMERCE - Septianto, Yulius; Pradiani, Theresia; Maskan, Mohammad (Journal of Management Small and Medium Enterprises (SMEs), 2025)
E-commerce has become one of the most significant phenomena in the digital era, marked by profound changes in how we conduct business, shop, and interact. The growth of e-commerce has brought many benefits, but there are also associated challenges. One of the main challenges is the increasing competition among e-commerce companies, both large and small. This study aims to analyze the impact of online promotional programs and service quality on consumer purchase decisions on Shopee in the Surabaya area and its surroundings, with customer trust in e-commerce as an intervening variable. The population of this study consists of Shopee consumers in Surabaya who have made at least two transactions on Shopee, with a sample of 100 respondents. The sampling technique used is purposive sampling, and the data analysis method used is path analysis with the SmartPLS 3 application. The results of the study show that 1) online promotion and service quality variables have a significant impact on customer trust and purchase decisions, 2) customer trust also significantly affects purchase decisions, 3) customer trust cannot serve as an intervening or mediating variable between online promotion or service quality and purchase decisions. Keywords: Online Promotion; Service Quality; Customer Trust; Purchase Decisions; Shopee